ANALISIS DAN EVALUASI SALURAN DRAINASE PADA KAWASAN PERUMNAS TALANG KELAPA DI SUB DAS LAMBIDARO KOTA PALEMBANG - Dimitri Fairizi (Jurusan Teknik Sipil Fakultas Teknik Universitas Sriwijaya, 2015)
Drainage system is a set of activities that form the effort to drain water whether it is runoff or underground water from an area or region. The purpose for this report is to analyze and evaluate the drainage channels in Perumnas Talang Kelapa Palembang. In the implementation of this report, the short-term rainfall data from 2001 to 2012 was used. The rainfall data was tested according to normal, log normal, log pearson III, and gumbel distribution. Select one result of those distribution with the smallest deviation standard. Then, it must be tested with the smirnov-kolmogorov test to find the rain intensity equation. That equation will be used to find the to plan the drainageÂ dimension. To analyze the incapacitated drainage, this report will use SWMM program. From the amount of 51 conduits in the SWMM model, there are 24 incapacitated conduits. To fix the conduits, the rational method will be used. Â Keyword : Drainage planning, standard of deviation, SWMM